Decoupling Conductivity and Solubility in Electrolytes Using Microemulsions. Issue 8 (4th August 2021) - Peng, Jing; Cantillo, Nelly M.; Xiao, Ye; Nelms, K. McKensie; Roberts, Lacey S.; Goenaga, Gabriel; Imel, Adam; Barth, Brian Andrew; Dadmun, Mark; Hayes, Douglas G.; Zawodzinski, Thomas
Abstract : Redox flow batteries have recently received considerable attention as possible large-scale energy storage devices, but their low energy density has inhibited widespread application. In this work, a novel strategy of decoupling conductivity and solubility of electrolytes using microemulsion is put forward to enhance ionic conduction of non-aqueous electrolytes, increase the selectivity of active species, improve the battery voltage, and eventually achieve the possibility of high energy density. We report a study of the electrochemistry of ferrocene in single phase Tween® 20/1-butanol/H2 O/toluene microemulsion system at 20 °C. At low and intermediate surfactant to water weight ratios (<0.5/0.5), the voltammogram exhibits reversible electrochemical behavior, while at high surfactant levels the curves show lower levels of reversibility. The latter voltammograms have a form typically associated with high resistance in solution, consistent with a gradual transition in microstructure as surfactant levels increase. This change in structure is supported by correlations with conductivity results based on the literature. The voltammograms show little evidence of anomalies in double layer capacitance or electrode "blocking" by droplets, suggesting that the electron transfer is indeed occurring in a facile manner between the electrode and the ferrocene inside the oil phase.